Calcium and cell function. - Cheung, Wai Yiu (Molecular biology.)
Calcium and Cell Function, Volume 7 covers the signal transduction across the cell membrane. The book discusses phosphoinositides and calcium signaling; calmodulin-stimulated adenylate cyclases; and calcium/calmodulin-dependent protein kinases. The text also describes the regulation of gene expression by calcium; the dynamics of intracellular calcium concentration during mitosis; and the methods for the measurement of intracellular ionized calcium in mammalian cells. Pharmacologists, physiologists, and people involved in the study of calcium and cell function will find the book invaluable.